Vegetation Condition and Potential Seed Rain in a Fire-Affected Tropical Forest Ecosystem Dominated by the Endangered Eucalyptus urophylla in Mutis Forest, East Nusa Tenggara-Indonesia: 10.32526/ennrj/24/20250151 - Damanik, Demak E.R.; Choesin, Devi N.; Sulistyawati, Endah (Environment and Natural Resources Journal, 2025)
Global deforestation and climate change-induced forest fires disrupt tropical forest functions. On the other hand, fires can be ecologically beneficial by increasing seed rain diversity and regeneration. In the Mutis forest, Indonesia, recurrent fires and deforestation threaten the endangered native species Eucalyptus urophylla. This study compared vegetation and seed rain between burned and unburned areas of the Mutis forest. Vegetation data were collected from 50 plots (10×10 m), in each area by measuring trees with a diameter at breast height (DBH; 1.3 m above ground level) ≥3 cm. Seed rain was collected for seven months using 50 seed traps (Ø 50 cm) in each area. The results showed that Eucalyptus urophylla has a significant ecological role in the both sites, as shown by its highest Importance Value Index (IVI) in both burned (177.05%) and unburned sites (115.70%). Four seed species were found in both sites, i.e., E. urophylla, Olea paniculata, Pittosporum timorense, and Rapanea hasseltii. The most abundant seeds were E. urophylla, 435 seeds at the burned site and 314 seed at the unburned site, indicating their origin from local vegetation. Seed species diversity was low in both burned (Shannon H'=0.21) and unburned (H'=0.39) areas. Therefore, conservation are necessary to maintain the sustainability of this forest. Recommended actions included seed collection in April to May, cultivation of E. urophylla for post-fire restoration, and implementing fire management strategies in the Mutis forest area.